Cost-effectiveness analysis of early antihypertensive treatment for hypertension detected at health screening - Hiromasa Ito; Tomohisa Seki; Toru Takiguchi; Yu Akagi; Kazumi Kubota; Kana Miyake; Masafumi Okada; Kazuhiko Ohe; Yoshimasa Kawazoe (Hypertension Research, 2026)
Abstract Background: Delayed initiation of antihypertensive therapy after the initial identification of hypertension during health checkups has been linked to an increased risk of cardiovascular disease. However, the long-term economic implications of this practice are not well understood. This study aimed to analyze the cost-effectiveness of early antihypertensive treatment. Methods: A Markov cohort model with four health states (baseline hypertension, acute cardiovascular disease (CVD), post-CVD, and death) was developed to project long-term outcomes for adults with screening-detected hypertension using data from the Japan Medical Data Center database, recorded January 2005–April 2021. Age-specific transition probabilities, CVD-related costs, and mortality were derived from a previously published cohort. Quality-adjusted life-years (QALYs) were estimated using utility values from prior literature. Early (<1 year) versus delayed (≥1 year) treatment initiation were compared across four age groups over a 20-year horizon from the healthcare payer perspective, applying a 2% annual discount rate. Deterministic and probabilistic sensitivity analyses assessed parameter uncertainty, and cost-effectiveness was evaluated against a willingness-to-pay threshold of ¥5 million per QALY. Results: In adults in their 40 s, early initiation yielded 13.52 QALYs and lifetime costs of ¥3,991,757, compared with 12.85 QALYs and ¥3,976,709 with delayed initiation, resulting in an incremental cost-effectiveness ratio of ¥22,489 per QALY. Early initiation remained highly cost-effective across all age groups, and probabilistic analyses demonstrated a high likelihood of cost-effectiveness. Conclusions: These findings support encouraging healthcare payers to use screening results proactively to promote early hypertension management and strengthen follow-up systems that reduce delays between detection and appropriate treatment.